Classroom Teacher’s Digital Literacy Level based on Instant Digital Competence Assessment (IDCA) Perspective - Idam Ragil Widianto Atmojo; Roy Ardiansyah; Wulandari Wulandari (Mimbar Sekolah Dasar, 2022)
Technological developments have made digital literacy one of the survival skills in the 21st century, which is linked to development of teacher core competencies, and digital literacy. This study aims to evaluate the level of digital literacy among teachers in the classroom. This descriptive qualitative case study involved 6 teachers at elementary school in Surakarta as the subjects which were chosen through purposive sampling by using digital literacy framework based on the Instant Digital Competence Assessment (IDCA) perspective. It classifies digital literacy into three dimensions, namely technology, cognitive, and ethics. The results showed that, on the technology dimension, 16.67% of the subjects were in the medium category, 50% in the low category, and 33% in the very low category. On the cognitive dimension, 33.33% of the subjects were in the moderate category, 16.67% in the low category, and 50% in the very low category. On the ethical dimension, 50% of the subjects were in the high category, 16.67% in the low category, and 33.33% in the very low category. Thus, it has been concluded that the digital literacy level of classroom teachers is in the very low to high categories.